A V2O5/conductive-polymer core/shell nanobelt array on three-dimensional graphite foam : a high-rate, ultrastable, and freestanding cathode for lithium-ion batteries - Shen, Zexiang (2014)
A thin polymer shell helps V2O5 a lot. Short V2O5 nanobelts are grown directly on 3D graphite foam as a lithium-ion battery (LIB) cathode material. A further coating of a poly(3,4-ethylenedioxythiophene) (PEDOT) thin shell is the key to the high performance. An excellent high-rate capability and ultrastable cycling up to 1000 cycles are demonstrated.